(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the efficacy and safety of Intralesional 5-fluorouracil in the treatment of cutaneous warts. METHODOLOGY: A descriptive cross-sectional investigation was undertaken at the Department of Dermatology, Chandka Medical College & Hospital, Larkana, with the objective of elucidating the therapeutic efficacy and tolerability profile of intralesional 5-fluorouracil (5-FU) in the management of cutaneous warts. The study population consisted of males and females aged between 18 and 65 years, all presenting with cutaneous warts of a minimum duration of one month. Participants received bi-weekly intralesional injections of 5-FU (50 mg/ml) until a maximum of six treatment sessions were administered. The therapeutic outcomes were classified as excellent (75-100% of cure), good (50-74% of improvement), fair (25-49% of improvement), or poor (<25% of improvement). The collected data were analyzed utilizing SPSS version 26, employing a significance level of 0.05. RESULTS: The study involved a sample of 129 subjects with an average age of 31.60±11.28 years. A substantial proportion of the participants (62.0%) fell within the age bracket of 18 to 30 years, and 64.3% of the individuals were classified as female. Following the administration of six intralesional injections of 5-fluorouracil, a remarkable 75.2% of the subjects exhibited considerable improvement, whereas 10.9% demonstrated a positive response, 7.8% a satisfactory result, and 6.2% an unfavorable outcome. Regarding safety, pain was the most frequent adverse effect (72.8%), followed by erythema (20.1%), and irritation (15.5%). CONCLUSION: Interlesional administration of 5-fluorouracil (5-FU) has been demonstrated to be an efficacious and safe intervention for the management of cutaneous warts; a majority of patients experienced significant clearance of lesions. The findings of this investigation further substantiate 5-FU as a cost-effective therapeutic alternative in the treatment of obstinate warts particularly in settings with limited resources. Furthermore, larger scale with long follow-up randomized controlled trials are necessary to validate these findings.